A bioenergetic basis for membrane divergence in archaea and bacteria. - Víctor Sojo (Public Library of Science (PLoS), 2014)
Membrane bioenergetics are universal, yet the phospholipid membranes of archaea and bacteria-the deepest branches in the tree of life-are fundamentally different. This deep divergence in membrane chemistry is reflected in other stark differences between the two domains, including ion pumping and DNA replication. We resolve this paradox by considering the energy requirements of the last universal common ancestor (LUCA). We develop a mathematical model based on the premise that LUCA depended on natural proton gradients. Our analysis shows that such gradients can power carbon and energy metabolism, but only in leaky cells with a proton permeability equivalent to fatty acid vesicles. Membranes with lower permeability (equivalent to modern phospholipids) collapse free-energy availability, precluding exploitation of natural gradients. Pumping protons across leaky membranes offers no advantage, even when permeability is decreased 1,000-fold. We hypothesize that a sodium-proton antiporter (SPAP) provided the first step towards modern membranes. SPAP increases the free energy available from natural proton gradients by ∼60%, enabling survival in 50-fold lower gradients, thereby facilitating ecological spread and divergence. Critically, SPAP also provides a steadily amplifying advantage to proton pumping as membrane permeability falls, for the first time favoring the evolution of ion-tight phospholipid membranes. The phospholipids of archaea and bacteria incorporate different stereoisomers of glycerol phosphate. We conclude that the enzymes involved took these alternatives by chance in independent populations that had already evolved distinct ion pumps. Our model offers a quantitatively robust explanation for why membrane bioenergetics are universal, yet ion pumps and phospholipid membranes arose later and independently in separate populations. Our findings elucidate the paradox that archaea and bacteria share DNA transcription, ribosomal translation, and ATP synthase, yet differ in equally fundamental traits that depend on the membrane, including DNA replication.